2015
DOI: 10.1016/j.eurpsy.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability and Omega-3 Index in Euthymic Patients with Bipolar Disorders

Abstract: Heart rate variability (SDNN) may provide a useful tool to study the impact of interventions aimed at reducing the increased risk of cardiovascular disease in euthymic patients with bipolar disorders. The difference in SDNN between cases and controls cannot be explained by a difference in the Omega-3 Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Parameters were calculated from a 30 min ECG recording, with SD of R–R interval (SDNN), low frequency (LF) power and high frequency (HF) power found to be lower in the BD group. 17 In 2012, Levy used several physiological measures of autonomic nervous system function to determine differences between patients with BD and healthy controls, without using the traditional HRV features. Thirty-three patients with BD and 22 healthy controls had 5 min of ECG recorded at rest, with significant differences found in physiological HR features between patients with BD and healthy controls.…”
Section: Presentationmentioning
confidence: 99%
“…Parameters were calculated from a 30 min ECG recording, with SD of R–R interval (SDNN), low frequency (LF) power and high frequency (HF) power found to be lower in the BD group. 17 In 2012, Levy used several physiological measures of autonomic nervous system function to determine differences between patients with BD and healthy controls, without using the traditional HRV features. Thirty-three patients with BD and 22 healthy controls had 5 min of ECG recorded at rest, with significant differences found in physiological HR features between patients with BD and healthy controls.…”
Section: Presentationmentioning
confidence: 99%
“…More recently, Voggt et al (2015) used 30-minute ECG recordings in 90 predominantly medicated bipolar I and II subjects combined, deemed ‘ clinically stable ’, and 62 healthy control subjects, to measure differences in HRV. They found that the SDNN, LF and HF parameters were lower in the bipolar subjects.…”
Section: Hrv and Euthymia In Bipolar Disordersmentioning
confidence: 99%
“…A reduced HRV has been found to predict an adverse prognosis in the general population, and is a strong and independent predictor of mortality after an acute myocardial infarction (Algra et al, 1993; Kleiger et al, 1987; Rennie et al, 2003). Several lines of evidence indicate autonomous dysfunction in bipolar disorder (Levy, 2013; Wang et al, 2016), and HRV has been found reduced during different affective states in patients with bipolar disorder compared with healthy control subjects in individual studies (Chang et al, 2014, 2015; Clarke, 2015; Cohen et al, 2003; Gruber et al, 2015; Henry et al, 2010; Lee et al, 2012; Levy, 2014; Moon et al, 2013; Quintana et al, 2015; Voggt et al, 2015). In the first focused systematic review and meta-analysis of HRV in bipolar disorder, we recently found support for a reduced HRV in patients with bipolar disorder compared with healthy control individuals although several methodological issues in individual studies limiting the evidence were identified (Faurholt-Jepsen et al).…”
Section: Introductionmentioning
confidence: 99%